The Lentil: Botany, Production and Uses 2009
DOI: 10.1079/9781845934873.0013
|View full text |Cite
|
Sign up to set email alerts
|

Origin, phylogeny, domestication and spread.

Abstract: This chapter describes the history, taxonomy (morphological and molecular), centre of origin, spread of culture, and evolution of the cultivated forms of lentil. Lentils were domesticated, in the Near East or, more accurately, in the foothills of the mountains of southern Turkey and northern Syria. The raw materials were populations of orientalis, but primitive farmers could also have used some other species of the genus, whose similarity has been shown in this chapter, in mixed populations rather than in pure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
33
0
14

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 0 publications
3
33
0
14
Order By: Relevance
“…considered: aristae presence or absence, stipule dentations and angle, peduncle/rachis length ratio, leaflet number of fully expanded leaves, and plant pubescence (Ferguson et al, 2000;Cubero et al, 2009). …”
Section: Morphological Datamentioning
confidence: 99%
“…considered: aristae presence or absence, stipule dentations and angle, peduncle/rachis length ratio, leaflet number of fully expanded leaves, and plant pubescence (Ferguson et al, 2000;Cubero et al, 2009). …”
Section: Morphological Datamentioning
confidence: 99%
“…Based on these observations, L. odemensis has been considered to be a member of secondary gene pool, and L. nigricans and L. ervoides were classifi ed in the tertiary gene pool (Ladizinsky 1993 ). Further, Cubero et al ( 2009 ) also suggested to place L. odemensis in secondary gene pool, while L. nigricans and L. ervoides can also be part of secondary gene pool as hybrids could be obtained by means of embryo rescue. They also suggested that there is a need to study hybridization in order to establish place of L. tomentosus and L. lamottei in secondary or tertiary gene pool.…”
Section: Crossability Groups and Gene Poolmentioning
confidence: 95%
“…Easy cross-compatibility of L. odemensis with L. culinaris could have generated the genetic raw material for western lentils having bigger seeds, a high number of large leafl ets and calyx teeth longer than corolla. The reports demonstrate that L. orientalis and L. odemensis forms are the most likely candidates as companion weeds of the cultigen, and disruption selection has only differentiated microsperma and macrosperma types during the course of evolution (Cubero et al 2009 ).…”
Section: Crop Systematic and Species Relationshipsmentioning
confidence: 97%
See 1 more Smart Citation
“…orientalis), L. odemensis, L. ervoides, L. nigricans, L. tomentosus and L. lamottei (van Oss et al 1997;Cubero et al 2009).…”
unclassified